ICT-BASED SIMPLE STAGES FOR UPDATING THE MAP OF VILLAGE’S FACILITIES - Goeritno, Arief; Hadi Purwanto, Eko; Eosina, Puspa (LPPM Univ. Ibn Khaldun Bogor, 2023)
This article explains about the utilization of information technology for updating the map of village’s facilities. The activity objectives are convey information about the stages of process and obtains a physical form of updated for the map of village’s facilities. A number of stages for the process is covers the preparation of the work team, submission of renewal permits for the map of village’s facilities, and comparison of secondary and primary data. The physical form of an updated the map of village’s facilities is a process of renewing and making a hard copy of the map of village facilities of A1 paper size along with a frame and scheduling and submission of a symbolic the map of village’s facilities to the Head for the Village of Pemagarsari.